2020
DOI: 10.1007/s10286-020-00733-x
|View full text |Cite
|
Sign up to set email alerts
|

Acute hyperhidrosis and postural tachycardia in a COVID-19 patient

Abstract: We describe a COVID-19 patient with acute hyperhidrosis and symptomatic orthostatic tachycardia. We encountered 3 other patients with ophthalmic dysautonomia. We posit COVID-19 as a cause of acute, limited, possibly dysimmune, autonomic dysfunction.A 39-year-old man, a construction worker with no medical history, was diagnosed with COVID-19 from nasopharyngeal swab reverse transcription polymerase chain reaction (rt-PCR) when he presented with 8 days of acute respiratory symptoms, diarrhea, abdominal discomfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 5 publications
3
47
0
1
Order By: Relevance
“…Furthermore, it is possible that the anti-SARS-CoV2 antibodies might have an autoimmune basis as they cross-react with the receptors in the ganglia [16]. Another case study found POTS in a SARS-CoV2 patient hypothesized that the virus reduces the ACE2 receptor when it binds and consequently increased sympathetic activity [17]. Given the nature of the aforementioned study findings, it is important to look at how COVID-19 and POTS are related.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, it is possible that the anti-SARS-CoV2 antibodies might have an autoimmune basis as they cross-react with the receptors in the ganglia [16]. Another case study found POTS in a SARS-CoV2 patient hypothesized that the virus reduces the ACE2 receptor when it binds and consequently increased sympathetic activity [17]. Given the nature of the aforementioned study findings, it is important to look at how COVID-19 and POTS are related.…”
Section: Discussionmentioning
confidence: 97%
“…This syndrome develops after acute stress factors, such as viral illness [ 19 21 ]. Therefore, dysautonomia, including postural tachycardia, has been determined in patients with COVID-19 [ 4 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…These symptoms, when combined with excessive orthostatic tachycardia, can lead to a diagnosis of postural tachycardia syndrome (POTS) post-COVID-19 [6]. Recently, a number of case reports have been published describing patients who developed POTS following a SARS-CoV-2 infection [7][8][9]. Anecdotal preliminary information from personal communications with autonomic clinics in the USA, UK and Canada suggest an increased incidence of POTS, with independent articles in the Wall Street Journal [10], The New York Times [11], and The Atlantic [12].…”
Section: Long-covid Potsmentioning
confidence: 99%